Dendritic cell proliferation by primary cilium in atopic dermatitis - Toriyama, Manami; Rizaldy, Defri; Nakamura, Motoki; Atsumi, Yukiko; Toriyama, Michinori; Fujita, Fumitaka; Okada, Fumihiro; Morita, Akimichi; Itoh, Hiroshi; Ishii, Ken J. (Frontiers in Molecular Biosciences, 2023)
Atopic dermatitis (AD) is a common allergic eczema that affects up to 10% of adults in developed countries. Immune cells in the epidermis, namely Langerhans cells (LCs), contribute to the pathogenesis of AD, although their exact role(s) in disease remain unclear. Here, we show that human dendritic cells (DCs) and LCs have a previously unknown primary cilium-like structure. The primary cilium was assembled during DC proliferation in response to the Th2 cytokine GM-CSF, and its formation was halted by DC maturation agents. This suggests that the role of primary cilium is to transduce proliferation signaling. The platelet-derived growth factor receptor alpha (PDGFRα) pathway, which is known for transducing proliferation signals in the primary cilium, promoted DC proliferation in a manner dependent on the intraflagellar transport (IFT) system. We also examined the epidermal samples from AD patients, and observed aberrantly ciliated LCs and keratinocytes in immature and proliferating states. Our results identify a potential relationship between the primary cilium and allergic skin barrier disorders, and suggest that targeting the primary cilium may contribute to treating AD.